2018
DOI: 10.29261/pakvetj/2018.082
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Repertoire and Antimicrobial Resistance Profile of Shiga Toxin-Producing E.coli Isolated from Sheep and Goat Farms from Al-buhayra Egypt

Abstract: Shiga toxin-producing E.coli (STEC) evokes a paramount concern from the public health point of view. Many reports dealt with the characterization of STEC from large ruminants. This study aimed to investigate the presence of STEC in sheep and goats, distribution of stx1, stx2, eaeA, and hlyA genes encoding Shiga toxins, intimin, enterohemolysins, and the antimicrobial resistance index (MAR). A total of 170 samples collected from (diarrheic, apparently healthy, and milk samples) from sheep, goats, and bedding (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
1
2
Order By: Relevance
“…In contrast to our finding, the prevalence virulence was Stx1 and eae genes [45]. Moreover, the previous study performed by Elsayed et al, [46] reported that both the Stx1 and Stx2 genes were highly prevalent. In our study the eae genes were noticed in 15.4% of E. coli isolates, which is in accordance with Ishii et al, [47] but is in contrast to [48] and [49].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our finding, the prevalence virulence was Stx1 and eae genes [45]. Moreover, the previous study performed by Elsayed et al, [46] reported that both the Stx1 and Stx2 genes were highly prevalent. In our study the eae genes were noticed in 15.4% of E. coli isolates, which is in accordance with Ishii et al, [47] but is in contrast to [48] and [49].…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, the present study reported that the E. coli isolates were sensitive to Tulathromycin, Ceftiofur, Marbofloxacin, Amikacin, Nalidixic acid, and Oxytetracycline with the percentages of (53.84%), (46.16%), (46.16%), (15.38%), (7.70%), and (7.70%) respectively. However, Elsayed et al, [46] established that STEC serotypes were highly sensitive to Chloramphenicol and doxycycline more than that of Ampicillin and Amoxycillin/clavulinic acid. The Shiga-toxin-producing E. coli can survive for a long time in the feces of cattle that constitute apotential for transmitting its toxins and antimicrobial resistance to other animals and human [52].…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance (AMR) was observed in STEC isolates against AMP (72%), TET (30 %), and SXT (9%); these percentages were lower in comparison to a study carried out in Turkey where a higher frequency of AMR to AMP and TET (100% and 50% respectively) was reported (Seker and Kus 2019). In Egypt, lower levels of AMR to AMP (66.7%) but higher to SXT (73.3%) were described in a goat slaughterhouse (Elsayed et al 2018). In Mexico, a study discovered 92% and 75% of AMR to AMP and TET respectively in bovines, this contrast with our study where both antibiotics showed a lower level of AMR.…”
Section: ; Carlos Et Al 2016)contrasting
confidence: 99%